Telaah Wacana Tekstual Pada Buku Teks Bahasa Indonesia Kelas VII SMP - Faizal Arvianto (Educatio, 2018)
Discourse analysis gives attention to the language in the text and context together in a communication. Discourse analysis does not only look at the structure of sentences but also meaning as an important element. Therefore, the interpretation of meaning is not only done in the statement in the text, but also the analysis of the hidden meaning. The surface structure in discourse is called grammatical aspect, while the internal structure is called the lexical aspect. In detail, the grammatical aspects of discourse include: reference, recovery, percolation, and sequence, while the lexical aspects of discourse include: repetition, synonyms, collocation, hyponym, antonyms, and equivalence. The text that became the subject of the analysis was short stories and narrative text in the â€œBuku Teks Bahasa Indonesia Kelas VII SMP Kurikulum 2013â€. Based on the results of the study, there are two parts of the grammatical aspects that are dominant, namely the reference and the conjunction. Lexically, this research found some lexical devices, they are repetition, synonym, antonym and collocation. The dominant device in emergence is repetition. There are two dominant repetitions, namely epizeuksis and anaphora repetition. After those two types of repetitions, the repetition appears frequently is noun repetition. Besides, the emergence of the second lexical aspect is collocation. Antonym and synonyms are in the third rank in the frequency of emergence after collocation. Each of these discourse cohesion devices forms a unified of whole and coherent discourse.